2019
DOI: 10.1097/aln.0000000000002955
|View full text |Cite
|
Sign up to set email alerts
|

Hydrocortisone Compared with Placebo in Patients with Septic Shock Satisfying the Sepsis-3 Diagnostic Criteria and APROCCHSS Study Inclusion Criteria

Abstract: Background: Two recent randomized controlled trials (Adjunctive Glucocorticoid Therapy in Patients with Septic Shock [ADRENAL] and Activated Protein C and Corticosteroids for Human Septic Shock [APROCCHSS]) of corticosteroids in patients with septic shock reported different treatment effects on 90-day mortality. Both trials enrolled patients who met the criteria for septic shock using the second international consensus definitions for sepsis and septic shock (Sepsis-2), but the APROCCHSS trial mandated a great… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 18 publications
0
6
1
Order By: Relevance
“…However, our findings should be taken with caution because the disease severity (sepsis vs septic shock or high vs low SOFA score) seemed to modify the association between corticosteroid treatments and the 28-day mortality in the Sepsis-3 cohort. Although our analysis showed that corticosteroids were not associated with reduced 28-day mortality, the post hoc analysis of the ADRENAL trial 16 showed that intravenous corticosteroid significantly reduced the 28-day mortality in patients who fulfilled the Sepsis-3 criteria for septic shock (odds ratio, 0.80; 95% CI, 0.64 to 0.99, p=0.04). In addition, the APROCCHSS trial, 2 which included patients with mean baseline SOFA score of 12—much higher than the SOFA score≥2 required by the Sepsis-3 criteria for sepsis—showed that corticosteroids were associated with reduced 90-day mortality (RR, 0.88; 95% CI, 0.78 to 0.99, p=0.03).…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…However, our findings should be taken with caution because the disease severity (sepsis vs septic shock or high vs low SOFA score) seemed to modify the association between corticosteroid treatments and the 28-day mortality in the Sepsis-3 cohort. Although our analysis showed that corticosteroids were not associated with reduced 28-day mortality, the post hoc analysis of the ADRENAL trial 16 showed that intravenous corticosteroid significantly reduced the 28-day mortality in patients who fulfilled the Sepsis-3 criteria for septic shock (odds ratio, 0.80; 95% CI, 0.64 to 0.99, p=0.04). In addition, the APROCCHSS trial, 2 which included patients with mean baseline SOFA score of 12—much higher than the SOFA score≥2 required by the Sepsis-3 criteria for sepsis—showed that corticosteroids were associated with reduced 90-day mortality (RR, 0.88; 95% CI, 0.78 to 0.99, p=0.03).…”
Section: Discussioncontrasting
confidence: 70%
“…11 Thus, the Sepsis-3 definitions were increasingly adopted by researchers and clinicians to ensure consistency in clinical studies and daily practice. 11 13-15 After the Sepsis-3 definitions were proposed, to the best of our knowledge, only one post-hoc analysis of the ADRENAL trial has applied the Sepsis-3 criteria for septic shock, 16 but the association between intravenous corticosteroids and mortality in patients with sepsis defined by the Sepsis-3 criteria has not yet been summarized. Thus, we aimed to conduct this systematic review and meta-analysis to summarize the efficacy of corticosteroids in patients with sepsis defined by the Sepsis-3 criteria.…”
Section: Introductionmentioning
confidence: 99%
“…trial using the inclusion criteria for the trial by Annane et al. showed no effect of corticosteroids on 90‐day mortality [70]. The mortality benefit observed by Annane et al.…”
Section: Corticosteroidsmentioning
confidence: 99%
“…Glucocorticoids are natural steroid hormones with pleotropic effects, including the upregulation of anti-inflammatory protein expression and downregulation of proinflammatory protein expression through binding of the transcription factor glucocorticoid receptor (GR). Since the first trial conducted in the 1960s, 24 randomized placebocontrolled trials have been published with conflicting results [59][60][61][62][63]. Factors affecting the response of a patient with sepsis to glucocorticoid treatment may have accounted for the conflicting results of the trials, including the time to treatment, dose and dosing strategy, type of glucocorticoid, other drugs administered, as well as patient comorbidities and genetic polymorphisms [64,65].…”
Section: Treatments Targeting Hyperinflammationmentioning
confidence: 99%